2015
DOI: 10.4085/1062-6050-50.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Facilitators of Professional Commitment in the Collegiate Setting

Abstract: Context: Professional responsibility, rewards and respect, and time for rejuvenation are factors supporting professional commitment for athletic trainers (ATs) in the high school setting. The inherent complexities of an occupational setting can mitigate perceptions of professional commitment. Thus far, evidence is lacking regarding professional commitment for ATs in other occupational settings.Objective: To extend the literature on professional commitment of the AT to the collegiate setting.Design: Qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The methods used in our study of collegiate ATs' perspectives on professional commitment were substantially the same as those previously described in Eason et al 17 We selected qualitative methods to allow participants to articulate their personal experiences and opinions related to their professional commitment. The paradigm was necessary to fully understand the concept of professional commitment because commitment is an individual concept and because the data within athletic training are limited.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in our study of collegiate ATs' perspectives on professional commitment were substantially the same as those previously described in Eason et al 17 We selected qualitative methods to allow participants to articulate their personal experiences and opinions related to their professional commitment. The paradigm was necessary to fully understand the concept of professional commitment because commitment is an individual concept and because the data within athletic training are limited.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [45][46][47] on professional commitment of ATs has shown that individuals in this profession are highly intrinsically motivated. Perhaps this motivation is a manifestation of certain personality traits common to ATs.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed these participants and their coworkers extra personal time for rejuvenation, a facilitator to individuals' professional commitment, as discussed in the literature. 35,37 Other participants enjoyed WLB practices by means of support from their supervisors. This included formal policies, like mandatory off days or personal hours worked into the schedule each day, and less formal ones like attention given to athletic trainers' WLB needs by their supervisors, sometimes providing early closing days.…”
Section: Organizational Level Factors and Worklife Balancementioning
confidence: 99%
“…A grasp of the affective and continuance components of professional commitment was most apparent in this group of participants. [35][36][37] Several of them outwardly weighed their passion for patient care interaction with the strain on their personal life, reaching a conclusion that departure from the profession or setting may be imminent. We found this to be mostly consistent with Kahanov's and Eberman's 4 suggestion of life stage in relation to workfamily conflict as a potential cause of departure from the profession and change in employment settings.…”
Section: Organizational Level Factors and Worklife Balancementioning
confidence: 99%